Evaluation of bond strength between ultra-high-performance concrete and normal strength concrete: an overview - Bibi Farouk, Abdulwarith Ibrahim; Haruna, S.I. (Penerbit Universiti Kebangsaan Malaysia, 2020)
Ultra-high-performance concrete (UHPC) is an advanced, durable cementitious material with excellent mechanical properties, which makes it an appropriate material for strengthening, repair, and retrofitting of damaged concrete structures. The UHPC as a repair material on normal strength concrete (NSC) depends on the quality of the bond strength at the interface. The interface behavior of UHPC-NSC concrete has a significant impact on its overall durability performance. This paper reviews the studies conducted on the bond strength at the concrete interface to determine the effectiveness of different bond strength testing techniques. The review has shown that the bond strength is commonly evaluated through splitting tensile, slant shear, direct shear, pull-off, bi-surface shear, and third-point flexural tests. Slant shear and splitting tensile test methods are the most common techniques used to evaluate the performance of bond strength between UHPC and NSC. splitting tensile tests, stress is directly applied at the concrete interface, while in the slant shear test, the interface surface is subjected to combined compressive stress and shear stress. Thus, Splitting tensile tests produces more accurate results than the slant shear test. Bi-surface shear and third-point flexural tests are easy to conduct and give a result similar to splitting and direct shear tests. However, further investigations are required on the reliability of the test methods under different conditions. In terms of failure modes, splitting tensile tests produces a more consistent result compared to the pull-off test.